CONDUCTIVE PATHWAYS CONSTRUCTION USING GENETIC ALGORITHM AND CONSTRUCTAL DESIGN - Avendano, P. A.; Souza, J. A.; Adamatti, D. F. (Revista de Engenharia Térmica, 2019)
In this work, Constructal Design and Genetic Algorithms are used to construct high conductivity paths connected to a heat sink and inserted in a square plate of low conductivity material with internal heat generation. The objective is propose a methodology that leads to minimize the maximum solid domain temperature. Total volume of the plate, amount of high thermal conductivity material and thermal ratio between high and low conductivities are fixed. The high conductive pathway forms found in this work greately resembles to the tree-forms found in nature, on which temperature is efficiently minimized by the application of the Genetic Algorithm and the Constructal Theory combined.